Adım motorlarının karakteristikleri ve bilgisayar ile konum kontrolü uygulaması - Apaydın, Hasbi (My University, 2006)
Adım Motorlarının Karakteristikleri ve Bilgisayar İle Konum Kontrolü Uygulaması Adım motorları diğer elektrik motorlarından farklı olarak sürekli bir dönme hareketi yerine, eşit büyüklükte adım açısı ile hareket edebilen bir elektro mekanik sistemdir. Adım motorları girişine uygulanan elektrik enerjisini adımsal mekanik enerjiye dönüştürebilmesi ve bu hareketin pozisyon denetiminde kolaylık oluşturması nedeniyle, günümüzde tercih edilen bir elektrik motoru olmuştur. Adım motoru uygulamalarında karşılaşılan en önemli problemlerin başında hiç kuşkusuz, bu motorların belirli şartlar altında sürülmesi ve kontrolü gelmektedir. 1930’lu yıllardan başlayan süreçle birlikte, teknolojideki gelişmeler ışığında sayısal bilgisayarların, mikroişlemcilerin ve otomatik kontrol sistemlerinin gelişmesi, hem tasarım hem de hareket açısından adım motorlarına büyük katkılar sağlamıştır, adım motorlarının kullanımı yaygınlaşmıştır. Adım motorunun kontrol ve sürme problemi tamamen adım motorlarının çalışması, yapısı, statik ve dinamik özelliklerinin iyi bilinmesini gerektirir. Yapılan bu tez çalışmanın II.,III.,IV. ve V. bölümlerinde sırasıyla step motorlarının çeşitleri, temel çalışma prensipleri, kontrol ve sürücü sistemleri, elektromanyetik yapısı ile statik ve dinamik karakteristikleri geniş biçimde açıklanarak bunlara ilişkin denklem ve matematiksel ifadelere yer verilmiştir.

The Characteristics of the Step Motors and the Placement Controlling Application by Computer The step motors are an electromechanical system which differ from other electrical motors due to their angularly movements to perform continuously rotation movement. The step motors are highly preferred in nowadays due to its ability of converting the electrical energy to the stepping mechanical energy and being necessary for the rotor position control of this kind of movement. The top of the most important matters met in the step motor application are unsuspiciously the driving under specific conditions and the controlling of these motors. Together with the process come along 1930’s the step motor control system instead of the electronic control systems have provided big contribution to the step motor both related to the design and movement, together with development of the numerical computers, microchips and automatic control systems in the light of the technological devolopments and the using of the step motors in the control systems of such structure draw attention to this way. The matter of the control and driving of the step motor leads the good knowledge about the working, structure and dynamical specifications of the step motors. In chapter II, III, IV and V various stepping motor, basic operation principles, control and driving device, electromagnetic structure, dynamic and static model are widely and respectively explained. In the VIth chapter of the works there has been contended a sample application related to the computer software and control of the step motor. In this chapter, there has been created cast model of a ventilating system and due to the providing the control of lid of the ventilating system the interface program has been performed by designing a microsupervisor hadware necessary for this system upon the model together with 0, 15, 30, 45, 60, 75 and 90 degree angles, connected to the computer via RS232 serial communicating port. In addition to control system matlab simulation of the step motor has been prepared and results have been compared with cost model. In the last chapter comments and results have been given in detail.
Keywords: Elektrik Eğitimi; Motorlar